Epstein-Barr Virus-Encoded BILF1 Orthologues From Porcine Lymphotropic Herpesviruses Display Common Molecular Functionality - Mavri, Maša; Kubale, Valentina; Depledge, Daniel P.; Zuo, Jianmin; Huang, Christene A.; Breuer, Judith; Vrecl, Milka; Jarvis, Michael A.; Jovičić, Eva Jarc; Petan, Toni; Ehlers, Bernhard; Rosenkilde, Mette M.; et al. (Frontiers in Endocrinology, 2022)
Infection of immunosuppressed transplant patients with the human γ-herpesvirus Epstein-Barr virus (EBV) is associated with post-transplant lymphoproliferative disease (PTLD), an often fatal complication. Immunosuppressed miniature pigs infected with γ-herpesvirus porcine lymphotropic herpesvirus 1 (PLHV1) develop a similar disease, identifying pigs as a potential preclinical model for PTLD in humans. BILF1 is a G protein-coupled receptor (GPCR) encoded by EBV with constitutive activity linked to tumorigenesis and immunoevasive function downregulating MHC-I. In the present study, we compared BILF orthologues encoded by the three known PLHVs (PLHV1-3) with EBV-BILF1 to determine pharmacological suitability of BILF1 orthologues as model system to study EBV-BILF1 druggability. Cell surface localization, constitutive internalization, and MHC-I downregulation as well as membrane proximal constitutive Gαi signaling patterns were conserved across all BILFs. Only subtle differences between the individual BILFs were observed in downstream transcription factor activation. Using Illumina sequencing, PLHV1 was observed in lymphatic tissue from PTLD-diseased, but not non-diseased pigs. Importantly, these tissues showed enhanced expression of PLHV1-BILF1 identifying this receptor as a suitable model GPCR for pharmacological intervention against PTLD in vivo.